Substantiation of the procedure for the reflection of goodwill in the accounting system of national enterprises - Izmaylov, Yaroslav (Technology audit and production reserves, 2017)
Goodwill is the amount that an enterprise buyer pays more than the book value of assets. According to foreign accounting practices, external goodwill arises only in the case of acquisition and combination of companies, and internally generated goodwill should not be reflected in the accounting of enterprises at all. The current methodology for reflecting goodwill in Ukraine has weak points, because of the lack of research and the lack of system, related to the novelty of the category and the lack of experience in accounting and reporting. The absence or non-reflection of information on goodwill in accounting leads to a decrease in the attractiveness of national enterprises in the markets for sales, labor, capital, resources, reduces costs, possibility of raising funds, searching for strategic investors and partners, building relationships with the authorities and shaping the demand and loyalty of consumers. An analysis of existing approaches to the accounting interpretation of goodwill with the proposal of classification is carried out. The prerequisites for introduction into accounting practice and gradual expansion of use in the national system of accounting for the goodwill of an enterprise are substantiated. A systematic treatment of positive goodwill for acquiring and combination of the enterprises is presented. The expediency of returning to use in the national accounting system of negative goodwill (badwill) is proved. The use of proposed proposals for the reflection of goodwill in the accounting system will allow national enterprises to increase the real book value, improve the investment-innovative attractiveness for investors, perform efficiency analysis and search for reserves of forming a positive business reputation.